PENGENDALIAN PERSEDIAAN BAHAN BAKU KARUNG PLASTIK (WOVEN) DI PT XYZ DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Suparjo; Rizky Sugiarto (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2021)
Raw material inventory is an important factor in the production process. Lack of raw materials will result in delays in the production process, on the other hand, excess raw materials will result in swelling storage costs and other costs. Through optimal inventory control, companies can determine the right order quantity by minimizing inventory costs. The purpose of this study was to determine and analyze the raw material inventory control implemented by PT. XYZ. This type of research is quantitative descriptive by describing how the company applies raw material inventory control through the data obtained and analyzed using the Economic Order Quantity (EOQ) method. The data used are primary data in the form of analysis and interviews. From the results of the calculation of the EOQ method and the policies carried out by the company, there is a significant difference in the cost of ordering Polypropyline, Caco3, and Additives raw materials with a cost difference of 40%. Therefore, the company can use a control strategy for ordering raw materials with the EOQ method for raw materials for Woven production that have experienced optimal expenditure compared to the strategies used by the previous company.